Local and Large-Range Inhibition in Feature Detection - Bolzon, Douglas M. (J Neurosci, 2009)
Lateral inhibition is perhaps the most ubiquitous of neuronal mechanisms, having been demonstrated in early stages of processing in many different sensory pathways of both mammals and invertebrates. Recent work challenges the long-standing view that assumes that similar mechanisms operate to tune neuronal responses to higher order properties. Scant evidence for lateral inhibition exists beyond the level of the most peripheral stages of visual processing, leading to suggestions that many features of the tuning of higher order visual neurons can be accounted for by the receptive field and other intrinsic coding properties of visual neurons. Using insect target neurons as a model, we present unequivocal evidence that feature tuning is shaped not by intrinsic properties but by potent spatial lateral inhibition operating well beyond the first stages of visual processing. In addition, we present evidence for a second form of higher-order spatial inhibition—a long-range interocular transfer of information that we argue serves a role in establishing interocular rivalry and thus potentially a neural substrate for directing attention to single targets in the presence of distracters. In so doing, we demonstrate not just one, but two levels of spatial inhibition acting beyond the level of peripheral processing.